Differences in Grading Systems Among Canadian Universities - Taylor, Hugh (Canadian Journal of Higher Education, 1977)
This study examines the great diversity of grading systems used in twenty-three of Canada’s largest universities. For analysis purposes the grading systems are divided into two main types. The first consists mainly of Ontario institutions using a percentage scale with the number of passing grades ranging from three to twelve. The second includes universities from nearly all sections of Canada where the four to ten passing grades are equated with either descriptive terms or grade-point categories. From the analysis various suggestions are offered which, if adopted, should greatly improve the communication value of grades and increase their effectiveness in decision-making.